2015
DOI: 10.1264/jsme2.me15046
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Swine Gut Microbiota in Response to Porcine Epidemic Diarrhea Infection

Abstract: The gastrointestinal tract of mammals is a complex ecosystem with distinct environments and comprises hundreds of different types of bacterial cells. The gut microbiota may play a critical role in the gut health of the host. We herein attempted to identify a microbiota shift that may be affected by porcine epidemic diarrhea (PED). We observed significant differences in microbiota between the control and PED virus (PEDV)-infected groups at both the phylum and genus level. Most commensal bacteria (i.e. Psychroba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
42
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 29 publications
5
42
3
2
Order By: Relevance
“…Whether is the microbiota influenced by FCoV presence, or if certain animals with peculiar microbiota composition are predisposed to FCoV infection is unclear. In literature, only two studies investigated the correlation between gut microbiota and coronaviral diseases, specifically in swine transmissible gastro-enteritis virus (TGEV) infection (Koh et al, 2015;Liu et al, 2015). However, results were not comparable with our findings because of the different pathogenic role of FCoV compared to TGEV, as FECV infection is usually asymptomatic, and because of the different diet and bacterial phylotypes observed in swine compared to cats.…”
Section: Discussioncontrasting
confidence: 94%
“…Whether is the microbiota influenced by FCoV presence, or if certain animals with peculiar microbiota composition are predisposed to FCoV infection is unclear. In literature, only two studies investigated the correlation between gut microbiota and coronaviral diseases, specifically in swine transmissible gastro-enteritis virus (TGEV) infection (Koh et al, 2015;Liu et al, 2015). However, results were not comparable with our findings because of the different pathogenic role of FCoV compared to TGEV, as FECV infection is usually asymptomatic, and because of the different diet and bacterial phylotypes observed in swine compared to cats.…”
Section: Discussioncontrasting
confidence: 94%
“…We observed a clear increase in the relative abundance of Proteobacteria and Fusobacteria in PEDV-infected suckling pigs. Fusobacteria increases have previously been observed in the feces of PEDV-infected suckling pigs [1,20,21]. Furthermore, many studies suggested that this phylum is associated with various clinical anaerobic infections (including in the mouth, teeth, gut, and brain) in humans, and is positively correlated with catarrhal appendicitis on the mucosal surface [38,39].…”
Section: Discussionmentioning
confidence: 91%
“…The timely treatment of PEDV-induced diarrhea and vomiting can effectively reduce mortality in newborn piglets [2]. Many previous researches [1,[21][22][23] linking specific bacteria to healthy versus infected piglets suggests that regulating intestinal microbiota is a promising method for PED treatment. Indeed, gut microbiota have been successfully used to prevent diarrhea [47].…”
Section: Discussionmentioning
confidence: 99%
“…In the gut, the protective effect of the innate immunity, in particular IFN-, is counteracted by intestinal commensal bacteria . PEDV infection causes the decrease of commensal bacteria normally present in the healthy gastrointestinal tract and induces an unbalanced shift of gut microbiota (Koh et al, 2015;Liu et al, 2015b), suggesting a possible modulation of IFNresponse by PEDV. The border surface of the intestinal epithelium is the major entry site for enteric viruses and specific mechanisms are needed for the fail-safe protection of such multi-layered surfaces.…”
Section: Roles Of Ifn-˛/ˇ and Ifn-in The Intestinementioning
confidence: 99%